2020
DOI: 10.1088/1742-6596/1666/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

On the ratcheting of the VT6 alloy in a range of loading scenarios

Abstract: A set of experimental results concerning the accumulation of inelastic strain in the VT6 titanium alloy is presented. The considered tests include cyclic stress-controlled loading with monotonically increasing stress amplitude and constant mean stress. The focus of the study is on the accurate phenomenological modelling of the complex material behaviour. Four different material models are employed to capture the phenomena of ratcheting and nonlinear kinematic hardening. Two models are of the Armstrong-Frederic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Here, η > 0 and m Perzyna > 0 are parameters of Perzyna's viscosity law; f 0 = 1 MPa. In the previous paper [19] it was shown that the classical Voce's law of isotropic hardening is inappropriate for the ratcheting of the VT6 alloy. Therefore, the evolution of the isotropic hardening R is modelled by a new law, which accounts both for hardening and softening:…”
Section: Materials Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…Here, η > 0 and m Perzyna > 0 are parameters of Perzyna's viscosity law; f 0 = 1 MPa. In the previous paper [19] it was shown that the classical Voce's law of isotropic hardening is inappropriate for the ratcheting of the VT6 alloy. Therefore, the evolution of the isotropic hardening R is modelled by a new law, which accounts both for hardening and softening:…”
Section: Materials Modelsmentioning
confidence: 99%
“…Remark. Differentiating (12) with respect to time and using (19), we obtain a well-known form of the Armstrong-Frederick equation:…”
Section: Materials Modelsmentioning
confidence: 99%
See 3 more Smart Citations